Prevention of brachial plexus injury—12 years of shoulder dystocia training: an interrupted time‐series study. (17th February 2015) - Crofts, JF; Lenguerrand, E; Bentham, GL; Tawfik, S; Claireaux, HA; Odd, D; Fox, R; Draycott, TJ
Abstract : Objective: To investigate management and outcomes of incidences of shoulder dystocia in the 12 years following the introduction of an obstetric emergencies training programme. Design: Interrupted time‐series study comparing management and neonatal outcome of births complicated by shoulder dystocia over three 4‐year periods: (i) Pre‐training (1996–99), (ii) Early training (2001–04), and (iii) Late training (2009–12). Setting: Southmead Hospital, Bristol, UK, with approximately 6000 births per annum. Population: Infants and their mothers who experienced shoulder dystocia. Method: A bi‐monthly multi‐professional 1‐day intrapartum emergencies training course, that included a 30‐minute practical session on shoulder dystocia management, commenced in 2000. Main Outcomes: Neonatal morbidity (brachial plexus injury, humeral fracture, clavicular fracture, 5‐minute Apgar score <7) and documented management of shoulder dystocia (resolution manoeuvres performed, traction applied, head‐to‐body delivery interval). Results: Compliance with national guidance improved with continued training. At least one recognised resolution manoeuvre was used in 99.8% (561/562) of cases of shoulder dystocia in the late training period, demonstrating a continued improvement from 46.3% (150/324, P  < 0.001) pre‐training, and 92% (241/262, P  < 0.001) in the early training period. In parallel there was reduction in the brachial plexus injury at birth (24/324 [7.4%, P  < 0.01], pre‐training, 6/262 [2.3%] early training, and 7/562 [1.3%] late training. Conclusions: There are significant benefits to long‐term, embedded training programmes with improvements in both management and outcomes. A decade after the introduction of training there were no cases of brachial plexus injury lasting over 12 months in 562 cases of shoulder dystocia.